Leadership Matters: Needs Assessment and Framework for the International Federation for Emergency Medicine Administrative Leadership Curriculum. Issue 3 (30th August 2020) - Tupesis, Janis P.; Lin, Janet; Nicks, Brett; Chiu, Arthur; Arbalaez, Christian; Wai, Abraham; Jouriles, Nic
Abstract: Objectives: The objective was to research and develop a novel curriculum on administrative leadership development within the discipline of emergency medicine (EM) with the goal of establishing and implementing it through the world's EM professional organizations. Methods: From 2016 to 2018 an assessment of different administrative and leadership programs was performed by researching and reviewing previously outlined curricula. Using the data from this assessment, a questionnaire was developed, that was subsequently sent to members of the International Federation for Emergency Medicine's (IFEM) listserv. Results: A total of 377 people from 38 different countries participated in the survey. The majority of respondents identified themselves as EM specialists (81%, 306/377), while others identified themselves as EM resident physicians (9.5%, 36/377) and non‐EM specialist physicians (4.5%, 17/377). A large majority of respondents articulated that there was a paucity of developed curricula focusing on leadership, administrative, and management principles within their institution, training program, or professional organization. Across all topic areas, fewer than 30% of polled individuals indicated that they had formal education related to individual and programmatic leadership development, change management, assessment methodology, negotiation skills, financial analysis, media relations, and health care policy. Quality improvement (QI) was the only curricular element that a majority of respondents had integrated into their clinical practice (61%). Qualitative data analysis of the narrative comments was performed with further evaluation of thematic components. Conclusions: The results of this study further support the findings that the majority of EM providers queried do not have a longitudinal curriculum that fosters administrative and leadership development nor advocate for its importance in relation to the quality of care. Given this gap, we propose that medical education at all levels—medical schools, EM resident/specialty training programs, and professional organizations—should consider creating administrative and leadership development programs. Additionally, development of any curriculum should require a global understanding of health care systems and awareness of the unique contexts of a given location and its available resources.